Benefits of Honey Supplementation for Enhancing Health and Athlete Performance - Faltus, Anita; Pawłuszkiewicz, Karolina; Mikołajczak, Michał; Korgiel, Matylda; Gaweł-Dąbrowska, Dagmara (Quality in Sport, 2025)
Introduction: Honey may be one of the oldest substances known to man. Throughout history, it has been used not only as a healthy sweetener, but also as a medical remedy for wound care, digestive disturbances, skin conditions, cough and many others. Contemporary research has focused on broadening our understanding of its mechanisms of action and exploring additional potential benefits of honey for both health and physical performance enhancement. Purpose of the work: The aim of this study is to evaluate existing research on the influence of honey supplementation on health, in both a protective and therapeutic capacity, as well as its potential in enhancing athlete physical performance and recovery. Materials and methods: A comprehensive literature search and analysis was conducted on PubMed, Scopus, Google Scholar and Science Direct databases, encompasing both clinical trials and studies on animal models. Results: This review establishes honey as a natural therapeutic agent not only for skin conditions, wound healing and cough relief, but also as a potential aid in managing various cardiovascular disorders. Nevertheless, further research is needed. Furthermore, we recognize honey as a cost-effective and reliable alternative to sports supplements, such as carbohydrate gels and sports drinks.